Food sovereignty and uncultivated biodiversity in South Asia [ essays on the poverty of food policy and the wealth of the social landscape - Majahara, Pharahada (Academic Foundation ; International Development Research Centre, 2007)
This publication explores the meaning of agriculture and guides the reader into new territory, where food, ecology, and culture converge. In the food systems of South Asia, the margin between cultivated and uncultivated biodiversity dissolves through women's day-to-day practice of collecting and cooking food, constituting a feminine landscape. The authors bring this practice to light, and demonstrate the value of food production and consumption systems that are localized rather than globalized. Based on extensive field research in India and Bangladesh, with and by farming communities, the book.